Medicinal plant biotechnology (CABI, 2010)
This book covers the current knowledge in the subject of medicinal plant biotechnology and discusses the various facets in the light of contemporary developments. The book is organized into 10 major sections: (1) plant biotechnology and medicine; (2) natural resource management (biodiversity conservation and genetic diversity screening); (3) micropropagation (quality assurance and quality control); (4) in vitro secondary metabolite production; (5) harnessing the potential of hairy root cultures and plant-microbe interactions; (6) metabolomics and metabolic engineering; (7) bioinformatics: interfacing biotechnology and bioinformatics; (8) molecular characterization of medicinal plants; (9) molecular farming; and (10) leads from chemistry, nanotechnology and pharmacology for future biotechnological interventions.